Enough Quantity: Time to Focus on Quality of Researchers in Pakistan - Ahmed, Muhammad (International Higher Education, 2017)
The education sector of Pakistan has progressed tremendously during the last 15 years, with the number of researchers and research papers increasing by 248 percent and 687 percent respectively. However, the quality of Pakistani research is still of uneven quality, partly due to the inexperience, incompetence, and corruption of faculty at national higher education institutions. Revising faculty hiring criteria, establishing a plagiarism- free research culture, enhancing training on research ethics, and involving more Pakistani scholars trained abroad in research are key steps toward preserving higher education in Pakistan.